PERANCANGAN FOODCOURT TEPIAN SUNGAI DI DESA SUNGAI TUAK KABUPATEN PASER - Hasanah, Ummi Uswatun; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
This writing aims to design a food court area in Sungai Tuak Village on the banks of the Kandilo River. This design can be done through a neo vernacular architectural approach that raises vernacular aspects in Paser Regency and can make a culinary tourism area that introduces regional local culture with the sadurengas concept taken from the Paser Regency vernacular architectural. This design aims to develop the development of a tourism center that can advance the economy of the paser community. This writing resulted in the following designs: 1) Design of a food court for micro, small and medium enterprises; 2) Provide facilities and infrastructure for open space on the banks of the river; 3) Redesign of Kandilo river pier facility